The Role of Police Investigators in Treating Criminal Actions of Corruption - Respati Kurniawan (Veteran Justice Journal, 2021)
Abstract To further ensure the implementation of a corruption-free government, Law Number 31 of 1999 concerning Eradication of Corruption Crimes, as amended by Law Number 20 of 2001 concerning Eradication of Corruption Crimes, is in lieu of Law Number 3 of 1971. The birth of the law -this law is expected to accelerate the growth of people's welfare, with a countermeasure against the evil nature inherent in corruption. The author uses an empirical juridical approach, which is an approach that is carried out by studying the law in fact in the form of attitudes, judgments, behaviors, which are related to the problems being studied and which are carried out by conducting research in the field. Based on the results of the research, it can be concluded that the investigation activity is a follow-up to the investigation which has more or less found the construction of criminal corruption incidents that have occurred. Constraints faced with the authority of police investigators are the limited number of Criminal Investigators; information received regarding criminal acts of corruption is still unclear and in detail; operational costs that have not met; lack of public legal awareness. Efforts to overcome the obstacles faced include gradually increasing the number of criminal investigators; accelerate all access so that information related to criminal acts of corruption is quickly absorbed by police investigators; the government needs to increase the budget post for operational costs, in order to facilitate the running of investigative activities; and the need to provide outreach to the public either directly or through electronic media or social media. Keywords: Investigators, Crime, Corruption